2008
DOI: 10.1007/s10798-008-9060-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive styles on 2D drafting and design performance in digital media

Abstract: This paper investigates the interactions between design students' cognitive styles, as measured by Riding's Cognitive Styles Analysis, and performance in 2D drafting and design tasks in digital media. An empirical research revealed that Imager students outperformed Verbalisers in both drafting and creativity scores. Wholist-Analytic cognitive style dimension was found to be independent from drafting and design performance. The study suggests that examining the cognitive styles of students in Computer Aided Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…For example, several participants wanted to include more visual materials in the LMS discussion forums and to be able to modify and annotate documents online. This finding is consistent with previous research that empirically demonstrated the importance of "visual thinking" in design (Pektas, 2010). Project-based discussions within a team entail exchanging a huge amount of information in several different formats (drawings, images, verbal communication, etc.).…”
Section: Discussionsupporting
confidence: 91%
“…For example, several participants wanted to include more visual materials in the LMS discussion forums and to be able to modify and annotate documents online. This finding is consistent with previous research that empirically demonstrated the importance of "visual thinking" in design (Pektas, 2010). Project-based discussions within a team entail exchanging a huge amount of information in several different formats (drawings, images, verbal communication, etc.).…”
Section: Discussionsupporting
confidence: 91%
“…Despite extensive use within creativity research, the use of the CAT as a measure of creativity within design research is relatively small. Over a 30-year period, for example, only 11 papers were related to design journals (Jeffries, 2012a), and on further review, only two papers operationalized the CAT in their research (Christiaans & Venselaar, 2005;Pektas, 2010). Building upon this 30-year CAT database, follow-up searches, identified 24 papers that made reference to both graphic design and the CAT.…”
mentioning
confidence: 99%
“…For example, designers need to associate algorithmic ideas with geometric problems as extensions from a previous idea.The solutionreflecting strategy is a kind of solution-driven strategy that is particularly effective for the generation of creative outcomes in parametric design.The text-based scripting environments, such as Maya Script Editor and Python may require trouble-shooting processes regardless of their expertise. At the early stages of design education, designers are often limited by their ability of mastering the design tools [39].That is, cognitive process may be influenced by a variety of factors such as personal experiences and design environments. However, even though S3's protocol exhibits features of both novices' and experts' behaviour, this designer's solution-reflecting strategy may have resulted in the highest score of the CAT assessment in terms of creativity.This may be because the solution-reflecting strategy often causes "unexpectedness" [44], which can be interpreted as novelty.…”
Section: Discussionmentioning
confidence: 99%
“…The various versions of CAT as an expert panel assessment [18] had several dimensions of criteria including creativity, technical, and aesthetic dimensions.The common criteria of the CAT procedure for measuring creativity of design products include novelty, value, and aesthetics. Pektas [39] utilised two criteria (creativity and technical quality) in his application of the CAT for the purpose of revealing the relationship between design students' cognitive styles and design performance in digital media. Chulvi et al [40] applied three aspects of the criteria: novelty, utility and creativity to broaden the understanding of the activity.The study reported here involved the use of four criteria: novelty, usefulness, complexity, and aesthetics.…”
Section: Consensual Assessment Techniquementioning
confidence: 99%